UJI EFEKTIVITAS TABIR SURYA (IN VITRO) EKSTRAK ETANOL DAUN UBI JALAR Ungu (Ipomoea Batatas (L.)) Varietas Antin-3 DARI DUA METODE PENGERINGAN DAUN YANG BERBEDA - Damaranie Dipahayu; Djamilah Arifiyana (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
UV solar radiation intensively caused damage to human skin. Purple sweet potato leaves (Ipomoea batatas (L.)) contain a high anthocyanin component which has a chromophore group with conjugated double bonds, thus absorbing electromagnetic radiation in UV and Visible wavelength, so it can be used as a natural source of sunscreen. The aim of this research was conducted to determine the SPF value of ethanolic extract of purple sweet potato leaves (Ipomoea batatas (L.)) Antin-3 variety from two different drying methods namely freeze-drying for 48 hours (EFD) and oven for 24 hours (EOV). The results of this study indicate that Antin-3 leaf extract (EFD) at a concentration (ppm) 900; 700; 500; 300; 100 respectively are SPF 30; 25; 17; 11 and 4, while (EOV) respectively are SPF 13; 10; 7; 4 and 1. Effectivity sunscreen represented as SPF values, above 15 were categorized as ultra protection; between 8 and 15 as maximal protection; between 6 and 8 as extra protection; between 2 and 4 as minimal protection. From the results of this study, it can be concluded that the method of freeze-drying even though it requires a longer time and costs more expensive than the oven method but provides protection for sunscreen 2.5 times higher.